2003
DOI: 10.1074/jbc.m210689200
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling-3 (SOCS-3), a Potential Mediator of Interleukin-6-dependent Insulin Resistance in Hepatocytes

Abstract: Interleukin-6 (IL-6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
397
8
16

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(438 citation statements)
references
References 57 publications
17
397
8
16
Order By: Relevance
“…In addition, SOCS3 inhibits insulin signalling as shown both in vitro and in animal models [35][36][37]. As reported previously, in this study IL-6 upregulated SOCS3 mRNA in HepG2 cells with the peak at 1 h post-induction [35] (Fig. 5c).…”
Section: Ilsupporting
confidence: 87%
“…In addition, SOCS3 inhibits insulin signalling as shown both in vitro and in animal models [35][36][37]. As reported previously, in this study IL-6 upregulated SOCS3 mRNA in HepG2 cells with the peak at 1 h post-induction [35] (Fig. 5c).…”
Section: Ilsupporting
confidence: 87%
“…Many studies have analysed this question, and these will only be summarised here. Immune mediators such as TNF-α and IL-6 can directly interfere with insulin signalling [99][100][101][102][103], and the binding of these cytokines to their cognate receptor on muscle cells or hepatocytes has been shown to induce an intracellular response that interferes with the ability of the insulin receptor to phosphorylate its intracellular targets. The cellular response to insulin is dampened in consequence.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…One well-described example of this is the induction of the protein suppressor of cytokine signalling-3 (SOCS-3) by IL-6 in hepatocytes. This protein associates with the insulin receptor and suppresses insulindependent receptor autophosporylation and IRS-1 phosphorylation [100]. SOCS-3 also binds to IRS-1 and IRS-2, leading to their ubiquitination and proteasomal degradation [104].…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%
“…Several reports have demonstrated that ectopic expression of SOCS3 may lead to insulin resistance (Senn et al 2003;Steppan et al 2005;Ye et al 2012;Jorgensen et al 2013). As shown in Fig.…”
Section: Discussionmentioning
confidence: 93%
“…SOCS3 is a member of the suppressors of cytokine signaling (SOCS) family, which is a recently discovered family of proteins associated with the inhibition of insulin receptor signaling (Senn et al 2003). Several reports have demonstrated that ectopic expression of SOCS3 may lead to insulin resistance (Senn et al 2003;Steppan et al 2005;Ye et al 2012;Jorgensen et al 2013).…”
Section: Discussionmentioning
confidence: 99%